Farmers’ Adoption of Rotational Woodlot Technology in Kigorobya Sub-County of Hoima District, Western Uganda - Buyinza, M.; Banana, A.Y.; Nabanoga, G.; Ntakimanye, A. (Ethnobotany Research & Applications, 2008)
This paper evaluates, using logistic and multiple regression analyses, the socio-economic factors that influence farmers’ decisions to adopt rotational woodlot technology in the farming systems of Uganda, based on a household survey carried out between May and December 2004, involving 120 farmers in Kigorobya sub-county, Hoima district. The analyses demonstrate that farmers make decisions about woodlot technology based on the household and field characteristics. The factors that significantly influenced the decision to adopt rotational woodlot technology included: gender, tree tenure security, seed supply, contact with extension and research agencies, soil erosion index, size of landholding, fuelwood scarcity, and main source of family income. To promote greater adoption of rotational woodlot technology, particular attention should be placed on the use of appropriate socioeconomic characterization, to better target technologies to areas with greater adoption potential.
Keywords: Farmers’ Adoption; Rotational Woodlot Technology; Hoima District